Ageing decreases the healing of wounds in the skin of alcohol-preferring rats - Martinez, Francisco Eduardo [UNESP]; Cassettaria, Lucas Langoni [UNESP]; Nicolaua, Nicoly Cassolato [UNESP]; De Barros Camargoa, Victória Mokarzel [UNESP]; De Almeida Chuffaa, Luiz Gustavo [UNESP]; Pinheiroa, Patricia Fernanda Felipe [UNESP]; Padovania, Carlos Roberto [UNESP]; Martinez, Marcelo (Mark Allen Group, 2022)
Objective: Alcohol consumption combined with ageing alters the healing process of the skin. We evaluated whether ageing decreases the healing of incisional wounds in the skin of Wistar rats of Universidade de Chile of variety B (UChB). Method: A total of 20 adult rats and 20 older UChB rats, divided into two groups which underwent surgical aggression in the anterior region of the abdomen, were used: G1, adult rats (100 days old, control) with water and 10% ethanol; G2, aged rats (540 days old, experimental) with water and 10% ethanol; evaluated at 4, 7, 14 and 21 days after surgery. Results: Ageing did not alter the rupture force and collagen elasticity and resistance. There were increases in telomerase with the implementation of cellular senescence, in interleukin 1-alpha (IL-1α) at 14 days of healing, in epidermal growth factor (EGF) at 14 and 21 days of healing with delayed growth and development of keratinocytes, also an increase of IL-β at 4 days, and decrease in tumour necrosis factor (TNFα) at 7 days, associated with chronic scarring. There was an increase in vascular endothelial growth factor (VEGF) at 4 and 7 days, responsible for the early vessels re-establishment. There was a decrease in transforming growth factor 2-beta (TGFβ2) and β3 at 4 and 7 days of healing respectively, and estradiol at 4 days. Conclusion: Ageing decreases the skin healing in incisional wounds in alcohol-preferring rats. Declaration of interest: The authors have no conflict of interest to declare.